Expression of calpain-like proteins and effects of calpain inhibitors on the growth rate of Angomonas deanei wild type and aposymbiotic strains - de Oliveira, Simone Santiago Carvalho (BMC Microbiol, 2015)
BACKGROUND: Angomonas deanei is a trypanosomatid parasite of insects that has a bacterial endosymbiont, which supplies amino acids and other nutrients to its host. Bacterium loss induced by antibiotic treatment of the protozoan leads to an aposymbiotic strain with increased need for amino acids and results in increased production of extracellular peptidases. In this work, a more detailed examination of A. deanei was conducted to determine the effects of endosymbiont loss on the host calpain-like proteins (CALPs), followed by testing of different calpain inhibitors on parasite proliferation. RESULTS: Western blotting showed the presence of different protein bands reactive to antibodies against calpain from Drosophila melanogaster (anti-Dm-calpain), lobster calpain (anti-CDPIIb) and cytoskeleton-associated calpain from Trypanosoma brucei (anti-CAP5.5), suggesting a possible modulation of CALPs influenced by the endosymbiont. In the cell-free culture supernatant of A. deanei wild type and aposymbiotic strains, a protein of 80 kDa cross-reacted with the anti-Dm-calpain antibody; however, no cross-reactivity was found with anti-CAP5.5 and anti-CDPIIb antibodies. A search in A. deanei genome for homologues of D. melanogaster calpain, T. brucei CAP5.5 and lobster CDPIIb calpain revealed the presence of hits with at least one calpain conserved domain and also with theoretical molecular mass consistent with the recognition by each antibody. No significant hit was observed in the endosymbiont genome, indicating that calpain molecules might be absent from the symbiont. Flow cytometry analysis of cells treated with the anti-calpain antibodies showed that a larger amount of reactive epitopes was located intracellularly. The reversible calpain inhibitor MDL28170 displayed a much higher efficacy in diminishing the growth of both strains compared to the non-competitive calpain inhibitor PD150606, while the irreversible calpain inhibitor V only marginally diminished the proliferation. CONCLUSIONS: Altogether, these results indicate that distinct calpain-like molecules are expressed by A. deanei, with a possible modulation in the expression influenced by the endosymbiont. In addition, treatment with MDL28170 affects the growth rate of both strains, as previously determined in the human pathogenic species Leishmania amazonensis and Trypanosoma cruzi, with whom A. deanei shares immunological and biochemical relationships.